New insights into the phenomenon of remissions and relapses in autoimmune diseases and the puzzle of benign autoantibodies in healthy individuals - Elkoshi, Zeev (Frontiers in Immunology, 2025)
The onset and relapse of autoimmune diseases (AIDs) are triggered by autoimmune attacks on target tissues. However, symptoms are unlikely to appear if damaged cells are rapidly replaced. Addressing the implications of this premise, the present work examines the balance between target tissue destruction and recovery rates as a key factor in the mechanisms of remissions and relapses in AIDs. The theory, supported by published clinical data, suggests that remissions are improbable in AIDs characterized by slow target tissue recovery. Conversely, a high recovery rate is a necessary (though not sufficient) condition for cycles of remission and relapse in AIDs. A high recovery rate of target tissue explains the tendency for remitting-relapsing disease, the likelihood of detecting autoantibodies in healthy individuals and the responsiveness to immunosuppressive drug treatments. Analyzing specific AIDs through the balance of tissue destruction and recovery yields several insights. For example, the difference between androgenic alopecia, a non-remitting-relapsing disease and alopecia areata, a remitting-relapsing AID, is elucidated. A new mechanism underlying relapses and remissions in alopecia areata based on hair follicle regeneration rate is proposed. It is suggested that mild Graves’ disease and remitting Hashimoto’s thyroiditis would be responsive to corticosteroids or immunosuppressant treatment, unlike more severe forms of these diseases. Additionally, it is proposed that the transition from remitting-relapsing multiple sclerosis to secondary progressive multiple sclerosis is associated with the depletion of brain compensatory reserves. Notably, it is concluded that exercise will not play a neuroprotective role in secondary progressive multiple sclerosis.